Management Analysis of the Korean State Education System - Dahlia Puspitasari; Teri Yanto; Yusuf (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Education has the aim of providing teaching to individuals or groups of people in order to try to meet the needs for knowledge and skills in facing challenges in everyday life. The education system in South Korea has become a model as a country that has the best education in the world with significant policy changes with the aim of achieving the country's progress through improving the quality of its education. The aim of this research is to analyze and describe the management of the education system in South Korea as a basis for other countries that will make changes to their education systems. This research uses library research by collecting data and information through searching for written sources related to the research topic. The results of this research show that in the aspects of learning management, personnel management, education financing management, management of educational infrastructure and community relations in education, the South Korean state has management and control of education with the best quality with the critical issues of education being a challenge for the country so that it can be evaluated. and strengthening the structure of quality education units.